2023
DOI: 10.1186/s40854-023-00499-x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network analysis of the day of the week anomaly in cryptocurrencies

Abstract: Anomalies, which are incompatible with the efficient market hypothesis and mean a deviation from normality, have attracted the attention of both financial investors and researchers. A salient research topic is the existence of anomalies in cryptocurrencies, which have a different financial structure from that of traditional financial markets. This study expands the literature by focusing on artificial neural networks to compare different currencies of the cryptocurrency market, which is hard to predict. It aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Yaya and Ogbonna (2019) examined thirteen cryptocurrencies and concluded that none of their returns are affected by the DoW anomaly, but the volatility of BTC is different on Mondays and Fridays. Tosunoglu et al (2023) employed an artificial neural networks (ANN) algorithm to explore the DoW impacts on BTC, Ethereum, and Cardano and observed that only BTC exhibited it. Lastly, Verma et al (2023) investigated the effect of DoW on six cryptocurrencies and did not find any statistically significant results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yaya and Ogbonna (2019) examined thirteen cryptocurrencies and concluded that none of their returns are affected by the DoW anomaly, but the volatility of BTC is different on Mondays and Fridays. Tosunoglu et al (2023) employed an artificial neural networks (ANN) algorithm to explore the DoW impacts on BTC, Ethereum, and Cardano and observed that only BTC exhibited it. Lastly, Verma et al (2023) investigated the effect of DoW on six cryptocurrencies and did not find any statistically significant results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Theiri et al (2022) contributed to this area of research by focusing on cryptocurrency liquidity during the Russia-Ukraine war, underscoring the crucial role of market liquidity in comprehending the day-of-the-week effect. Tosunoğlu et al (2023) advanced the literature by employing artificial neural networks to analyze the day-of-the-week anomaly in cryptocurrencies, offering insights into the predictability of various currencies. Furthermore, Bae and Kim (2022) explored robust anomaly scores in cryptocurrencies, highlighting the impact of network factors on cryptocurrency returns.…”
Section: Sonal Sahumentioning
confidence: 99%
“…The ongoing debate over the value and role of cryptocurrencies has been fueled by contrasting views among prominent figures in the business and investment communities (Bazzanella and Gangemi 2023;Wu et al 2021;Xiao et al 2021;Xie et al 2019;Tosunoğlu et al 2023). On May 22, 2021, Elon Musk, the founder of SpaceX and CEO of Tesla, tweeted his support for cryptocurrencies, declaring a "battle" between digital currencies and fiat currencies.…”
Section: Introductionmentioning
confidence: 99%